¬¬¬Assessment of Pregnant’s Knowledge whose Attending Tishreen University Hospital about Smoking Effects on Pregnancy and it’s Outcome - نظام عفاف (Latakia University Journal -Medical Sciences Series, 2022)
Smoking during pregnancy doubles the risk of having a low-birth-weight baby, the rate of perinatal diseases and many other negative pregnancy outcomes. Recent statistics indicate a high proportion of smokers, especially among the young group; Which raises concern about the future health problems of the mother and pregnancy outcome. The aim of the study is assessment pregnant’s knowledge whose attending Tishreen University Hospital about smoking effects on pregnancy and it’s outcomes. The questionnaire was distributed to 100 pregnant women who visited gynecological clinic in the hospital during the period from 5/5/2019 to 12/7/2019. The results indicated that 70% of the study sample do not know that smoking increases the rate of Gestation Diabetes Meletus (GDM), 84% of them do not know and are not sure that it causes premature rupture of membranes, and an increased risk of sudden infant death, 46% don’t know that it reduces milk production and causes early weaning, and about 60% of them didn’t know that it causes an obesity among their children, diabetes type II, and increases the risk of heart disease when they reach adulthood. The total knowledge level about smoking harms among two-fifths of the sample ranged between low and medium level. The study recommended the necessity of activating the role of the educational media about smoking’s harms to the pregnant woman and her fetus, designing awareness brochures for high school and university female students and women attending health centers and outpatient clinics in hospitals, and qualifying nurses to perform their educational role on the same topic.